Implementasi dan Prespektif Hukum Bagi Pekerja Yang Tidak Melaksanakannya Employee Branding - Rohmah, Siti Afidatul; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In today’s increasingly competitive global business landscape, employee branding has emerged as a strategic approach for companies to build and maintain a positive public image through their workforce. In the digital era, particularly with the rise of social media, every action and communication by employees—both online and offline—can influence the company's reputation. This study aims to examine the legal consequences for employees who fail to uphold employee branding in line with corporate standards and expectations, especially within the framework of Indonesian labor law. The research focuses on clarifying the legal boundaries, employee obligations, and protections for individual rights, including freedom of expression. Using a normative-juridical approach, this study seeks to provide a balanced understanding between a company’s interest in safeguarding its reputation and the rights of employees in the employment relationship. The findings are expected to contribute to the development of fair corporate policies aligned with national labor law principles.